Properties of chemically modified gelatin films - Carvalho, R. A. de [UNESP]; Grosso, C. R. F. (Brazilian Society of Chemical Engineering, 2006)
Edible and/or biodegradable films usually have limited water vapor barriers, making it difficult to use them. Thus, the objective of this work was to evaluate the effect of a chemical reticulation treatment with formaldehyde and glyoxal on the mechanical properties, water vapor permeability, solubility and color parameters of gelatin-based films. Formaldehyde and glyoxal were added to the filmogenic solution in concentrations ranging from 3.8 to 8.8 mmoles/100 mL of filmogenic solution and 6.3 to 26.3 mmoles/100 mL of filmogenic solution, respectively. The treatments caused a reduction in permeability to water vapor and in solubility. Only the treatment with formaldehyde caused a significant increase in rupture tension for concentrations above 6.3 mmoles/100 mL of filmogenic solution. Scanning electron microscopy indicated a loss of matrix orientation due to the chemical reticulation treatment.
Keywords: Films gelatin formaldehyde glyoxal